Optimization of Purchase Decisions for Vario Motorcycles through Product Quality Improvement and Safety Perception - Sri Pujiyama Pasaribusi; Rizka Asrina; Mustafa Khamal Rokan; Arsyadona Arsyadona (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
In the increasingly competitive automotive industry, motorcycle companies are required not only to deliver high-quality products but also to ensure that their products have distinct advantages over competitors. This study aims to analyze the influence of product quality and safety perception on the purchase decisions of Honda Vario motorcycles among students of the State Islamic University of North Sumatra (UINSU) and the surrounding community. The research method used is a participatory approach, with the study population consisting of UINSU students who are currently using or have used Honda Vario motorcycles. Data were collected through purposive sampling, involving 30 respondents. The results of the study indicate that product quality has a significant impact on purchase decisions, while safety perception does not show a significant influence. These findings underscore the importance of innovation and quality control in enhancing product competitiveness. Furthermore, transparency in addressing safety issues and providing optimal after-sales service were also identified as crucial factors in maintaining consumer trust. A comprehensive and integrated marketing strategy is recommended to enhance consumer loyalty and support the growth of Honda Vario sales.